2020
DOI: 10.29309/tpmj/2020.27.02.3406
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Diabetic Retinopathy in patients with Type-II diabetes mellitus in an upscale clinic in Karachi.

Abstract: Objectives: The objective of this study is to measure the current frequency of diabetic retinopathy in Karachi and the stage at which they present first to the outpatient department. Study Design: Cross sectional study. Setting: A private clinic setup in Karachi. Period: 1st July 2015 to 30th June 2016. Material & Methods: In this study, 440 eyes of 220 diabetics were included and frequency of diabetic retinopathy was measured. Individuals ranging from 20 – 80 years age were included. Ophthalmic plus syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The range of age in this study was from 30 to 75 years with mean age of 51.099±6.19 years, mean duration of diabetes 9.304±3.60 years and mean weight was 87.713±7.63 Kg as shown in Table - One study revealed that insulin intake was indirectly proportional to the presence of DR, as revealed by the landmark studies as well. 8 , which may point to a theory that good glycemic control is achieved with insulin which reduces the complication of DR. Our study has revealed strong association between levels of FBG and presence/absence of DR (p=0.003). Similar to other study in South Asia 9 revealed 8% DR cases, where FBG was <100mg/dl, may have resulted due to poor metabolic control before or because of longer duration of DM.…”
Section: Resultsmentioning
confidence: 99%
“…The range of age in this study was from 30 to 75 years with mean age of 51.099±6.19 years, mean duration of diabetes 9.304±3.60 years and mean weight was 87.713±7.63 Kg as shown in Table - One study revealed that insulin intake was indirectly proportional to the presence of DR, as revealed by the landmark studies as well. 8 , which may point to a theory that good glycemic control is achieved with insulin which reduces the complication of DR. Our study has revealed strong association between levels of FBG and presence/absence of DR (p=0.003). Similar to other study in South Asia 9 revealed 8% DR cases, where FBG was <100mg/dl, may have resulted due to poor metabolic control before or because of longer duration of DM.…”
Section: Resultsmentioning
confidence: 99%
“…One of its frequent and significant side effects, diabetic retinopathy (DR), is one of the main factors causing blindness globally 3 . A patient may have type 2 diabetes long before a clinical diagnosis is confirmed, and the condition is often diagnosed together with diabetic retinopathy [4][5] . The term diabetic retinopathy (DR) refers to damage caused by prolonged hyperglycaemia to the retinal microvascular system 6 .…”
Section: Introductionmentioning
confidence: 99%
“…DME can be introduced at any phase of DR and give ground to distortion of vision and abatement down visual sharpness 7,8 . The prevalence of NPDR is about 25.4%, and PDR is almost 1.4% globally 9,10 . The common symptoms of DR are visual impairment, dark black spots, and defects in the field of vision 7,8 .…”
Section: Introductionmentioning
confidence: 99%